Gastric Emptying in Critically Ill Children. (September 2017) - Martinez, Enid E.; Pereira, Luis M.; Gura, Kathleen; Stenquist, Nicole; Ariagno, Katelyn; Nurko, Samuel; Mehta, Nilesh M.
Background: Delayed gastric emptying (GE) impedes enteral nutrient (EN) delivery in critically ill children. We examined the correlation between (a) bedside EN intolerance assessments, including gastric residual volume (GRV); (b) delayed GE; and (c) delayed EN advancement. Materials and Methods: We prospectively enrolled patients ≥1 year of age, eligible for gastric EN and without contraindications to acetaminophen. Gastric emptying was determined by the acetaminophen absorption test, specifically the area under the curve at 60 minutes (AUC60 ). Slow EN advancement was defined as delivery of <50% of the prescribed EN 48 hours after study initiation. EN intolerance assessments (GRV, abdominal distension, emesis, loose stools, abdominal discomfort) were recorded. Results: We enrolled 20 patients, median 11 years (4.4–15.5), 50% male. Sixteen (80%) patients had delayed GE (AUC60 <600 mcg·min/mL) and 7 (35%) had slow EN advancement. Median GRV (mL/kg) for patients with delayed vs normal GE was 0.43 (0.113–2.188) vs 0.89 (0.06–1.91), P = .9635. Patients with slow vs rapid EN advancement had median GRV (mL/kg) of 1.02 mL/kg (0.20–3.20) vs 0.27 mL/kg (0.06–1.62), P = .3114, and frequency of altered EN intolerance assessments of 3/7 (42.9%) vs 5/13 (38.5%), P = 1. Median AUC60 for patients with slow vs rapid EN advancement was 91.74 mcg·min/mL (53.52–143.1) vs 449.5 mcg·min/mL (173.2–786.5), P = .0012. Conclusions: A majority of our study cohort had delayed GE. Bedside EN intolerance assessments, particularly GRV, did not predict delayed GE or rate of EN advancement. Delayed gastric emptying predicted slow EN advancement. Novel tests for delayed GE and EN intolerance are needed.